2018
DOI: 10.1101/474643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Application of UV-cured resin as embedding/mounting media for practical, time-saving otolith specimen preparation

Abstract: 19Otoliths are calcified structures located in the inner ears of fish, as in most vertebrates, 20 that are responsible primarily for the perception of gravity, balance and movement, and 21 secondarily of sound detection. Microstructural and chemical analyzes of the inner otolith 22 growth layers, called increments, constitute powerful tools to estimate fish age and 23 elucidate many life history and demographic traits of fish populations. Otolith analyzes 24 often require the production of a thin cross section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A total of 56, 35, and 38 fish were chosen for the 2014, 2015, and 2016 year-classes, respectively, including both normal and phenotypic/ genotypic sex mismatches. The sagittal otoliths were extracted from the heads, cleaned in distilled water, dried, and mounted in otolith grinding orientation blocks using UV-cured resin (Tama-Koubou) (see details in Strüssmann, Miyoshi, & Mitsui, 2018). The otoliths were oriented in the blocks so as to allow grinding through the transversal plane and production of a thin cross-section including the otolith core that is already present at birth.…”
Section: Estimation Of the Birth Dates And Thermal History Of Normamentioning
confidence: 99%
“…A total of 56, 35, and 38 fish were chosen for the 2014, 2015, and 2016 year-classes, respectively, including both normal and phenotypic/ genotypic sex mismatches. The sagittal otoliths were extracted from the heads, cleaned in distilled water, dried, and mounted in otolith grinding orientation blocks using UV-cured resin (Tama-Koubou) (see details in Strüssmann, Miyoshi, & Mitsui, 2018). The otoliths were oriented in the blocks so as to allow grinding through the transversal plane and production of a thin cross-section including the otolith core that is already present at birth.…”
Section: Estimation Of the Birth Dates And Thermal History Of Normamentioning
confidence: 99%
“…Micscape, www.microscopy-uk.org.uk/mag/ art97/locmount.html). A number of recent studies have shown good suitability of such media for pollen samples (Noetinger et al, 2017), wool, calcareous and siliceous microfossils (Phillips, 2020), fish otoliths (Strüssmann et al, 2018) etc. Introduction of these adhesives to industrial and household practice was enhanced by their relative safety along with fast and controlled curing (Bachmann & Cantor, 1999;Goss, 2002).…”
Section: Embedding Media Used In Light Microscopymentioning
confidence: 99%
“…Introduction of these adhesives to industrial and household practice was enhanced by their relative safety along with fast and controlled curing (Bachmann & Cantor, 1999;Goss, 2002). Their additional microscopy-related advantages are absence of solvents and hardeners, low viscosity, no need for heating, satisfactory chemical inertness in cured state, including neutral pH and compatibility with dyes, high hardness and transparency, intentionally strong adhesion to glass (e.g., due to silane additives: Goss, 2002;Vitale et al, 2018), refractive index close to that of glass (Tennent & Townsend, 1984;Punge, 2009), absence of fluorescence and absence of significant deterioration with time (including crystallization, leakage and damaging by living organisms), traced during 35 years in some cases (Silverman, 1986;Neuhaus et al, 2017;Noetinger et al, 2017;Strüssmann et al, 2018;Phillips, 2020).…”
Section: Embedding Media Used In Light Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Their properties vary and must be adapted to the required analysis and sample type, which means the cross-section has limited use. The specific properties of resins cover hot/cold preparation, curing time and temperature 37 , 38 , transparency 39 , colour, fluorescence 40 , hardness, edge retention, and viscosity influencing the infiltration 36 . When in contact with the sample, the resin has an impact on it.…”
Section: Introductionmentioning
confidence: 99%